(3GdeHGMK GdCUdjI Yf LedI GdWQjbI GdUhajIs - (3CHh GdYHGS CMeO Hf eMeO Hf jhSa GdJLjHj GdaGSj, GHf GdHfGA GdSQbSWjs
(3ChdgG (B:s
(3HSe GdEdg ai GdCehQ CHOC EP gh ZGjh dgG heHOC s
(3BNQgG (B:s
(3hGdMeO ddg GdPi NJefG HMeO Gddg ceG Hg HOGfG s
(3GdfSNI HgG MhGTs
(3eUOQ GbJfGA GdCUd (B:s
(3GdQHGW (B- (3GdeZQH (B(984 D) s
Keywords: (3GdJUha hGdBOGH GdTQYjIs